Social Reproduction in the Implementation of the Free Nutritious Food Program (MBG) in Makassar Early Childhood Education (PAUD) - Sangaji, Ayu Indira; Kamaruddin, Syamsu A; Adam, Arlin (JUPE : Jurnal Pendidikan Mandala, 2025)
This article aims to analyze how the implementation of the Free Nutritious Food (MBG) program in Early Childhood Education (PAUD) institutions in urban areas of Makassar reflects the process of social reproduction. Using Pierre Bourdieu’s theoretical framework of habitus, capital, and field, this article examines how practices and policies within the MBG program contribute to the perpetuation of social structures and class differences in society. The study adopts a conceptual–analytical approach, employing qualitative methods based on literature review and sociocultural analysis of the Makassar community context. The findings indicate that the MBG program functions not only as a child health policy but also as a symbolic arena that reinforces disparities in social, cultural, and economic capital among different social groups. Family habitus, perceptions of nutrition, and the ways educational institutions interpret policy collectively shape patterns of social reproduction within the urban context of Makassar. This article highlights the importance of a sociological approach in formulating child nutrition policies to foster more equitable social transformation..